Life in Labour (to the 170th anniversary of Ivan Pulyuy’s birth) - Kozyrsky, V. G.; Rokitsky, O. M.; Schenderovsky, V. A. (Physics and Chemistry of Solid State, 2015)
February 2, 2015 marked 170 years since the birth of the renowned scientist and patriot of Ukraine - Ivan Pulyuy. This name comes back to us from oblivion, like many other bright and outstanding figures that were forced to work outside of Ukraine against their will. Fundamental research in physics and electrical engineering, popular scientific and journalistic works, memories of Ivan Pulyuy, a talented physicist, thoughtful philosopher, sincere Ukrainian patriot, are very topical today, when Ukraine establishes its independence.